INDIVIDUAL DIFFERENCES BETWEEN L2 USERS AND L2 LEARNERS - Temurbek Saidnazarov; Dr. Raluca Marginas (International Scientific and Current Research Conferences, 2023)
Language learning is believed to have been central to personal and professional growth. However, there is much progress made in education, the gap between L2 users and L2 learners is still challenging language instructors. In order to identify the differences which causes some trouble, and to suggest a few relevant solutions we decided to conduct an experiment on students who are a senior doctor as well as a schoolboy. As regards the results, we found out several peculiarities of each person in terms of their abilities, attitude and the like relying on observations.